Sistem Budaya, Sistem Sosial, Sistem Perilaku, dan Sistem Kepribadian dalam Cerpen 'Lapdog Days' Karya Lana Citron (Cultural, Social, Behavioural, and Psychological Systems in Lana Citron’s 'Lapdog Days') - Hadiyanto Hadiyanto (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2018)
This paper discusses cultural, social, behavioral, and personality system in Lana Citron’s 'Lapdog Days'. The approach used in this research is eclectic approach by combining more than one research approach and is endorsed with Talcott Parsons’s Action Theory to analyze phenomena in the short story. The result of this research indicates that cultural, social, behavioral, and personality system are reflected in teenagers’ life of the characters in the short story namely, I, Sean, Niamh, Frederick and other characters.